The cell–DEVS formalism as a method for activity tracking in spatial modelling and simulation. (10th April 2015) - Wainer, Gabriel A.
The spreading of wildfires in forests is a complex natural phenomenon that depends on many different variables (such as the fuel, the geography of the area, the weather, etc.). We discuss different methods based on DEVS and cell–DEVS, which can be used to speed up the simulation and simplify the modelling of this kind of spatial system. We propose using a combination of quantised DEVS and dead reckoning to vary the length of the time steps taken by each cell. We also discuss different methods to adjust the computation method dynamically according to the level of activity, varying the length of the time taken by each cell. We show how these methods can be used to track the level of activity in the model automatically, without intervention by the modeller, and how this can improve the simulation performance for fire spreading and other environmental models. We show how the same models can be applied to a parallel simulation environment, allowing finding varied results faster than real–time.